Emergent non–image-guided resuscitative endovascular balloon occlusion of the aorta (REBOA) catheter placement: A cadaver-based study. Issue 3 (September 2016) - Linnebur, Megan; Inaba, Kenji; Haltmeier, Tobias; Rasmussen, Todd E.; Smith, Jennifer; Mendelsberg, Ranan; Grabo, Daniel; Demetriades, Demetrios
Abstract : BACKGROUND: Emergent resuscitative endovascular balloon occlusion of the aorta (REBOA) insertion for critically injured patients in hemorrhagic shock is performed blindly with fluoroscopic imaging confirmation. The aim of this study was to determine a reliable method for initial REBOA catheter insertion with balloon deployment between the left subclavian artery takeoff and the celiac trunk (CT). METHODS: Human cadaver study. External surface (sternal notch, mid-sternum, xiphoid) and intravascular (left subclavian artery [LSA], and CT) landmarks were measured from standardized left and right common femoral artery puncture sites. The landing zone (LZ, distance between LSA and CT) and margins of safety (distance from distal balloon edge to LSA and proximal balloon edge to CT) were calculated using intravascular landmarks. The probability of balloon deployment in the LZ using external landmarks was compared in univariate analysis using the Fisher exact test. RESULTS: Ten cadavers were analyzed (seven males; mean body mass index, 19.4 kg/m 2 ). Mean (SD) intravascular distances from femoral puncture sites to the LSA and CT were 54.8 (1.9) cm and 32.9 (1.9) cm. The mean (SD) LZ was 21.8 (3.8) cm. Mean (SD) surface distances from femoral puncture sites to the xiphoid, mid-sternum, and sternal notch were 31.8 (3.9) cm, 41.8 (3.3) cm, and 51.8 (3.2) cm. Inserting the catheter to a distance approximated by surface distance from the femoral puncture site to mid-sternum resulted in a 100% likelihood balloon deployment in the LZ for both sides. This was superior to the xiphoid and sternal notch (left site, p = 0.005; right site, p = 0.036; mean of both sites, p = 0.083). Using the mid-sternum landmark, the mean (SD) margins of safety to the LSA and CT were 10.7 (4.3) cm and 3.1 (3.4) cm. CONCLUSION: When using the use of the mid-sternum landmark for REBOA balloon placement, the likelihood of balloon deployment in the LZ was 100% with an acceptable margin of safety.